Impact of BAFF Blockade on Inflammation, Germinal Center Reaction and Effector B-Cells During Acute SIV Infection - Borhis, Gwenoline; Trovato, Maria; Ibrahim, Hany M.; Isnard, Stephane; Le Grand, Roger; Bosquet, Nathalie; Richard, Yolande (Frontiers in Immunology, 2020)
Memory B-cell dysfunctions and inefficient antibody response suggest germinal center (GC) impairments during HIV/SIV infection with possible contribution of overproduced B-cell activating factor (BAFF). To address this question, we compared proportions and functions of various B-cell subsets and follicular helper T-cells (TFH) in untreated (Placebo) and BR3-Fc treated (Treated) SIV-infected macaques. From day 2 post-infection (dpi), Treated macaques received one weekly injection of BR3-Fc molecule, a soluble BAFF antagonist, for 4 weeks. Whereas, the kinetics of CD4+ T-cell loss and plasma viral loads were comparable in both groups, BAFF blockade delayed the peak of inflammatory cytokines (CXCL10, IFNα), impaired the renewal of plasmacytoid dendritic cells and fostered the decline of plasma CXCL13 titers after 14 dpi. In Treated macaques, proportions of total and naïve B-cells were reduced in blood and spleen whereas SIV-induced loss of marginal zone (MZ) B-cells was only accentuated in blood and terminal ileum. Proportions of spleen GC B-cells and TFH were similar in both groups, with CD8+ T-cells and rare Foxp3+ being present in spleen GC. Regardless of treatment, sorted TFH produced similar levels of IL21, CXCL13, and IFNγ but no IL2, IL4, or BAFF and exhibited similar capacities to support IgG production by autologous or heterologous B-cells. Consistently, most TFH were negative for BAFF-R and TACI. Higher proportions of resting and atypical (CD21lo) memory B-cells were present in Treated macaques compared to Placebo. In both groups, we found higher levels of BAFF-R expression on MZ and resting memory B-cells but low levels on atypical memory B-cells. TACI was present on 20-30% of MZ, resting and atypical memory B-cells in Placebo macaques. BAFF blockade decreased TACI expression on these B-cell subsets as well as titers of SIV-specific and vaccine-specific antibodies arguing for BAFF being mandatory for plasma cell survival. Irrespective of treatment, GC B-cells expressed BAFF-R at low level and were negative for TACI. In addition to key information on spleen BAFF-R and TACI expression, our data argue for BAFF contributing to the GC reaction in terminal ileum but being dispensable for the generation of atypical memory B-cells and GC reaction in spleen during T-dependent response against SIV.